1998
DOI: 10.4018/joeuc.1998040102
|View full text |Cite
|
Sign up to set email alerts
|

What We Know About Spreadsheet Errors

Abstract: Although spreadsheet programs are used for small "scratchpad" applications, they are also used to develop many large applications. In recent years, we have learned a good deal about the errors that people make when they develop spreadsheets. In general, errors seem to occur in a few percent of all cells, meaning that for large spreadsheets, the issue is how many errors there are, not whether an error exists. These error rates, although troubling, are in line with those in programming and other human cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
202
0
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(241 citation statements)
references
References 62 publications
5
202
0
10
Order By: Relevance
“…The use of Excel spreadsheets and macros is probably not the optimum approach to maintain complex databases such as this (e.g., see Panko, 1998), but completely changing the implementation would require more support than is currently available. Ideally, maintaining such a database should be part of the larger efforts to improve emissions inventories or to develop and maintain improved modules for models, but at present this is not considered a part of either effort.…”
Section: Discussionmentioning
confidence: 99%
“…The use of Excel spreadsheets and macros is probably not the optimum approach to maintain complex databases such as this (e.g., see Panko, 1998), but completely changing the implementation would require more support than is currently available. Ideally, maintaining such a database should be part of the larger efforts to improve emissions inventories or to develop and maintain improved modules for models, but at present this is not considered a part of either effort.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, there are papers that address common errors in spreadsheets, like [19], [20], together with their causes.…”
Section: Related Workmentioning
confidence: 99%
“…Many researchers have examined error rates in spreadsheets, and Panko (2008) reported that in 13 audits of real-world spreadsheets, an average of 88% contained errors. Popular spreadsheet programs also make certain types of errors easy to commit and difficult to rectify.…”
Section: Introductionmentioning
confidence: 99%